Configuration 5S: a bi-directional AC-DC converter - Cipriano dos Santos Júnior, Euzeli (Eletrônica de Potência, 2012)
This paper proposes a bi-directional ac-dc converter to be applied in Energy-Control-Center (ECC) in order to interface dc variables, such as battery energy storage system and ac conventional utility grid. Such power electronic solution guarantees: (i) bi-directional power flow between dc and ac converter sides, (ii) independent control in both sides, (iii) high level of integration, and (iv) implementation of two functions using a unique power conversion stage. Despite proposing a new solution, this paper presents an analysis of the converter in terms of: PWM strategy, dc-link capacitor variables, switches variables, low-pass-filter specification employed at the output converter sides and a comparison with a conventional solution. Simulation and experimental results are presented as well.